Knowledge and Dealing Strategies Regarding Learning Disability in Students Among Teachers at Selected Schools of Jodhpur - Varsha Dhama; Aashish Parihar; Vandna Pandey; Raj Rani (Indian Journal of Psychiatric Nursing)
Background: Learning disability is a heterogeneous group of disorders manifested by significant difficulties in the acquisition and use of listening, speaking, reading, writing, reasoning, or mathematical abilities. Literature reports that in India prevalence of learning disability is 10% and there is approximately 90 million people with varying degrees of learning disabilities. Teachers play an important role in identifying and managing learning disabilities by using proper dealing strategies. Aim: The aim of this study is to assess the knowledge and dealing strategies regarding learning disabilities in students among teachers. Methods: 250 teachers who were engaged in teaching students from 1st to 5th standards were selected by convenient sampling technique from selected schools of Jodhpur. Results: A self-structured knowledge questionnaire found that 62.4% of teachers had inadequate and 37.6% had adequate knowledge regarding learning disabilities. Self-structured dealing strategy rating scale had seven domains and out of them, the preventive dealing strategies domain are more evidently used by the teachers as compared to other domains. Conclusions: Study concluded that most of the teachers had inadequate knowledge regarding the learning disability and there is a great need to plan and implement awareness program for teachers about learning disabilities.